2010
DOI: 10.5424/sjar/2010082-1199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grape seed extract on growth performance, protein and polyphenol digestibilities, and antioxidant activity in chickens

Abstract: Grape seed extract (GSE) provides a concentrated source of polyphenols that have antioxidant capacity. An experiment was conducted to investigate the effect of GSE at levels 0.6, 1.8 and 3.6 g kg -1 in broiler chicks (1 to 42 days) on growth performance, relative weights (pancreas, spleen and liver) and lengths (duodenum, jejunum, ileum and ceca) of digestive organs, relative weights of liver fat and abdominal fat, ileal protein digestibility, excreta extractable polyphenol digestibility, and antioxidant activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
88
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 25 publications
16
88
3
Order By: Relevance
“…Easily oxidized low-molecular-weight phenolic compounds, such as quercetin and gallic acid, probably deliver prooxidant effects, whereas high-molecular--weight phenolic compounds, such as procyanidins, have little or no prooxidant activity (Hagerman et al 1998). In fruit pomaces, the polyphenols are generally bound to fibre and are released by bacteria in the lower gastrointestinal tract (Brenes et al 2010), which decrease their pro-oxidant capacity in comparison with low-molecular-weight polyphenols that are absorbed in the upper gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Easily oxidized low-molecular-weight phenolic compounds, such as quercetin and gallic acid, probably deliver prooxidant effects, whereas high-molecular--weight phenolic compounds, such as procyanidins, have little or no prooxidant activity (Hagerman et al 1998). In fruit pomaces, the polyphenols are generally bound to fibre and are released by bacteria in the lower gastrointestinal tract (Brenes et al 2010), which decrease their pro-oxidant capacity in comparison with low-molecular-weight polyphenols that are absorbed in the upper gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Research results indicate that plant polyphenols could be a new source of antioxidants in animal diets (Brenes et al, 2010, Sahin et al 2010, Kamboh and Zhu 2013. The dietary grape seed extract has been found to contribute to and modulate the antioxidant activity of broiler chicken diets and excreta (Brenes et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peepre et al (2014) found that vitamin C, VE, and turmeric extract increase the plasma T3 and T4 concentrations of Wistar rats. Grape seed extract is a concentrated source of polyphenols, which have antioxidant capacity (Brenes et al, 2010). The live performance results observed in the present study may be attributed to the antioxidant capacity of VE and GSE, protecting thyroid hormones from oxidative degradation.…”
Section: Discussionmentioning
confidence: 64%
“…Grape seed extract has antioxidant effects as it contains polyphenolic compounds (Brenes et al, 2010), such as procyanidins, catechins, epicatechins, gallocatechins, and epigallocatechins (Chamorro et al, 2013). However, grape seed extract has been seldom evaluated in broiler feeding.…”
Section: Lipid Peroxidation In the Plasma Lungs Heart And Liver Of mentioning
confidence: 99%